2014
DOI: 10.1016/j.aap.2014.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Emergency healthcare worker sleep, fatigue, and alertness behavior survey (SFAB): Development and content validation of a survey tool

Abstract: Background: Workplace safety is a recognized concern in Emergency Medical Services (EMS). Ambulance crashes are common and injury rates exceed that of the general working public. Fatigue and sleepiness during shift work pose a safety risk for patients and EMS workers. Changing EMS worker behaviors and improving alertness during shift work is hampered by a lack of instruments that reliably and accurately measure multidimensional beliefs and habits that predict alertness behavior. Objectives: We sought to test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 51 publications
(89 reference statements)
1
19
0
2
Order By: Relevance
“…We developed a real‐time, text‐message based assessment and intervention tool for research purposes known as SleepTrackTXT [Patterson, Moore et al, ]. As a first step to determine the usefulness of our tool, we planned a pilot trial to examine the tool's performance, which included assessing participant compliance (responsiveness) with answering text‐message queries and participant satisfaction with the study tool.…”
Section: Introductionmentioning
confidence: 99%
“…We developed a real‐time, text‐message based assessment and intervention tool for research purposes known as SleepTrackTXT [Patterson, Moore et al, ]. As a first step to determine the usefulness of our tool, we planned a pilot trial to examine the tool's performance, which included assessing participant compliance (responsiveness) with answering text‐message queries and participant satisfaction with the study tool.…”
Section: Introductionmentioning
confidence: 99%
“…From 1980 to 2016 only seven studies involving shift workers reported comparisons of outcomes stratified by 12 and 24‐h shift durations . The need for research comparing outcomes by 12‐h and 24‐h shifts is compelling, especially given that the majority of EMS shifts are 12 and 24 h in duration . Among these studies, only three reported on measures of performance.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 The participant also completed the Sleep Fatigue and Alertness Behavior (SFAB) survey; a 50-item survey that measures eight components of alertness behavior while on duty. 16 The participant’s scores on the PSQI, ESS, CFQ, and OFER indicate he suffers from poor sleep quality, excessive daytime sleepiness, severe work related fatigue, and high levels of acute fatigue, chronic fatigue, with possibly poor recovery between scheduled shifts. The SFAB survey tool is new, and at the present time there is no benchmark or base rate from which to compare the participant’s SFAB score taken at baseline.…”
Section: The Casementioning
confidence: 99%